Training of Healthcare Workers for Bio Medical Waste Disposal in India: Issues, Challenges and Future Strategy - Prosad Konar, Anindya; Solanki, Kavita (Journal of Neonatal Surgery, 2025)
Biomedical waste management poses significant challenges to India's public health infrastructure, with improper handling and disposal potentially leading to serious environmental contamination and health hazards. This comprehensive analysis examines the critical aspect of training healthcare staff for effective biomedical waste disposal in India. Various studies reveal concerning gaps in knowledge, attitude, and practices (KAP) particularly among sanitary and auxiliary staff who directly handle waste on a daily basis. Key issues identified include inadequate training programs, poor segregation practices, regional disparities in infrastructure, and insufficient integration of waste management principles in healthcare education. The analysis further explores challenges such as infrastructure and resource limitations, resistance to behavioral change, monitoring difficulties, and the additional burden imposed by the COVID-19 pandemic. The researchers have tried to explore future strategies including comprehensive training approaches targeting different categories of healthcare workers, technological integration for improved training and monitoring, public-private partnerships, certification systems, and stronger institutional mechanisms. It has been realised that effective training is not merely a regulatory requirement but a fundamental necessity for ensuring occupational safety, public health protection, and environmental conservation. The researchers have tried to point out some key suggestions for policymakers, healthcare administrators, and educational institutions to enhance biomedical waste management training, thereby addressing this critical component of sustainable healthcare delivery in India.